Correlation of neck and wrist circumference with waist circumference - Karki, B.B.; Bhattarai, M.D.; Bajracharya, M.R.; Karki, S; Devkota, A.R. (Journal of Advances in Internal Medicine, 2015)
Background and aims: Body mass index, waist and hip circumference have been using for measurement of obesity, however practically it’s difficult to get these measures accurately because of the various reasons, so an alternative to this could be neck and wrist circumference measurement. As there is scarce report on such anthropometric studies from Nepal, we aimed to find out the correlation between neck and wrist circumference with waist circumference for obesity measure. Method: A cross sectional observational study of total 297(147 male and 150 female) participants, aged above 18 years conducted on 2013 at Kathmandu valley. Anthropometric markers of obesity were measured, including body weight, height, waist, hip, neck and wrist circumferences. Results: A strong positive Pearson correlation of neck circumference with waist circumference was found in both male and females(r=0.64 in male and r=0.86 in female). Neck circumference had strong positive correlation with waist circumference in obese female than in male(r=0.5 in male and r=0.82 in female).Similarly, neck circumference had positive correlation with body mass index(r=0.53in male and r=0.79 in female),hip(r=0.54in male and r=0.76in female), weight(r=0.59in male and r=0.77in female) except waist hip ratio(r=0.59in male and r=0.10in female). Neck circumference cutoff for abnormal waist (>=90cm for male and >=80cm for female) was 34.4cm for male and 32.5 cm for female. Similarly wrist circumference had also positive correlation with waist circumference(r=0.58 and r=0.64 in female) and with weight(r>0.6) in both sexes. Conclusion: Neck circumference which can be relatively easily measured has shown strong correlation with waist. Journal of Advances in Internal Medicine 2014;3(2):47-51.